A numerical simulation of air distribution in an office room ventilated by 4-way cassette air-conditioner - Bamodu, Oluleke; Xia, Liang; Tang, Llewellyn (Elsevier, 2017)
The work in this paper involves the investigation of an office room in cooling mode ventilated by a 4-way cassette air-conditioner, which is increasingly being installed in Eastern China. A comparison of the 4-way cassette AC is made against a typical wall-mounted mixing ventilation system based on ADPI calculations as well as difference in air temperature and velocity. The results in this paper, which are carried out by computational fluid dynamics (CFD) simulation, indicate that a superior air distribution performance is achieved by the 4-way cassette AC when compared to the wall-mounted system. The results also show potentials for energy saving using the 4-way cassette AC.